Superoxide-producing thermostable associate from the small intestines of control and alloxan-induced diabetic rats: quantitative and qualitative changes - R. M. Simonyan; K. V. Simonyan; G. M. Simonyan; H. S. Khachatryan; M. A. Babayan; M. H. Danielyan; L. V. Darbinyan; M. A. Simonyan (BMC Endocrine Disorders, 2022)
Abstract Background: NADPH oxidase 1 (Nox1), which is highly expressed in the colon, is thought to play a potential role in host defense as a physical and innate immune barrier against commensal or pathogenic microbes in the gastrointestinal epithelium. Diabetes can be caused by several biological factors, including insulin resistance is one of them. Alloxan is widely used to induce insulin-dependent diabetes in experimental animals. Alloxan increases the generation of reactive oxygen species as a result of metabolic reactions in the body, along with a massive increase in cytosolic calcium concentration. Methods Using a universal method, a superoxide radical (О2 −)-thermostable associate between NADPH-containing lipoprotein (NLP) and NADPH oxidase (Nox)- NLP-Nox was isolated and purified from the small intestine (SI) of control (C) and alloxan-induced diabetic (AD) albino rats. Results In comparison to the C indices, in AD in the SI, an increase in the specific content of NLP-Nox associate and a decrease in the stationary concentration of produced О2 − in liquid phase (in solution) and gas phase (during blowing by oxygen of the NLP-Nox solution) were observed. The NLP-Nox of SI associate in C and AD rats produced О2 − by an immediate mechanism, using NLP as a substrate. The phenomenon of the hiding of the optical absorption maxima of the Nox in oxidized states at pH10,5 was observed in the composition of these SI associates of the C and AD rat groups. The characteristic absorption maxima of the «hidden» Nox were observed under these conditions after reduction by potassium dithionite. Conclusion Thus, at AD, the decrease in the stationary concentration of produced О2 − in the solution and gas phase was compensated for by an increase in the specific amount of associate. In addition,  the decrease in the stationary concentration of produced О2 − by NLP-Nox associates at AD can be linked to a decrease in the level of NADPH in NLP-Nox composition. This could be used as a new mechanism of AD pathogenesis.